Unpredictable maternal sensory signals in caregiving behavior are associated with child effortful control - Holmberg Eeva; Kataja Eeva-Leena; Davis Elysia Poggi; Pajulo Marjukka; Nolvi Saara; Lahtela Hetti; Nordenswan Elisabeth; Karsson Linnea; Karlsson Hasse; Korja Riikka (PLOS, 2023)
Emerging evidence suggests that exposure to unpredictable patterns of maternal sensory signals during infancy is associated with child neurodevelopment, including poorer effortful control. However, longitudinal effects on child development and possible sex differences are understudied. The aims of the present study were to explore whether exposure to unpredictable maternal sensory signals during infancy is related to child effortful control at 5 years of age and whether child sex moderates these associations. In addition, we examined how exposure to very high vs. low/moderate unpredictability using categorical cut-offs is related to child effortful control. Participants (133 mother–child pairs, all Caucasian) were drawn from the FinnBrain Birth Cohort Study in Finland. Maternal sensory signals (auditory, visual, tactile) were coded from the 10-min free-play episode on a moment-on-moment basis using Observer XT 11 (Noldus), and the unpredictability of maternal sensory signals was characterized as the entropy rate when the infant was 8 months of age. Child effortful control was assessed via mother reports using the Child Behavior Questionnaire very short form (CBQ-VSF) when the child was 5 years old. Correlational analyses showed that higher unpredictability of maternal sensory signals had a modest association with children’s poorer effortful control at 5 years of age. Notably, the linear regression model showed that child sex moderated these associations, as higher exposure to unpredictable maternal sensory signals was related to poorer effortful control among males, but not among females. Moreover, the general linear model showed that exposure to very high unpredictability was associated with poorer child effortful control at 5 years of age and remained significant when adjusted for possible confounding factors. These results are in line with previous findings and suggest that the unpredictability of maternal sensory signals is potentially an important aspect of early caregiving behavior associated with the development of child effortful control.